2020
DOI: 10.32491/jii.v19i2.494
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies description of Halmahera epaulette shark endemic species (Hemiscyllium halmahera, Allen & Erdmann, 2013) in North Maluku Sea

Abstract: Halmahera Epaulette Shark (Hemiscyllium halmahera) is an endemic fish in the North Maluku sea. This species was first discovered in two spots of Halmahera waters namely Ternate and Bacan in 2013. Halmahera Epaulette Shark research was continue in Weda and Kao Bay in 2016, 2017 and 2018. Those previous studies, however, did not reveal the morphological description of this species in the other part of the Halmahera Islands. This research was made to enhance the information about this species from the other part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
1
7
0
2
Order By: Relevance
“…External conditions such as coral reefs, seagrasses, and mangroves as habitats and bioecological areas need support. The results study are similar to those found [21], [22], [30], [42], [47]. Clasper morphology and female genitalia in the Hemiscylliidae family have high similarity [21], [48].…”
Section: Data Samplessupporting
confidence: 89%
See 1 more Smart Citation
“…External conditions such as coral reefs, seagrasses, and mangroves as habitats and bioecological areas need support. The results study are similar to those found [21], [22], [30], [42], [47]. Clasper morphology and female genitalia in the Hemiscylliidae family have high similarity [21], [48].…”
Section: Data Samplessupporting
confidence: 89%
“…Morphometrics. The morphometric variables were measured using a 100 cm ruler on the TL (total length), SL (standard length), HL (head length), HW (head width), PFL (pectoral fin length), AFL (anal fin length), DFL (dorsal fin length), LTL (lower tail length), BC (body circumference) [22], [30] Figure 2. The morphometric data were tabulated using Microsoft Excel and analyzed.…”
Section: 22mentioning
confidence: 99%
“…Documentation of the H. halmahera was taken at 11 am on 8 April 2022 at a depth of 7 m during the only sighting recorded with a GoPro 10 Action Camera with an automatic underwater setting. The temperature recorded at the sighting time was 29 o C. Photographs and video stills were taken during the encounter and were identified based on morphological features based on several scientific publications focusing on this species [1], [3], [4]. Based on the documentation (Figures 3 and 4), we distinguished its species by its shape and colour pattern [1].…”
Section: Methodsmentioning
confidence: 99%
“…The Total length of this species is not more than 80 cm according to Allen et al 2013, and another study by Madduppa et al 2013 shows a maximum TL of 74 cm and an average TL of 52.3±10.2 cm for both species (N=32). The recorded depth of this species is mostly around 3-10 m [1], [3], [4], with a maximum depth recorded at 18 m in other studies [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation